PENGARUH KEPERCAYAAN ATAS MEREK TERHADAP LOYALITAS NASABAH PADA BANK BTPN KCP KABANJAHE - Charisma Kuriata Ginting S (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
This research aims to determine the extent of the influence of brand trust on customer loyalty to the Bank BTPN KCP Kabanjahe. To withstand the competition, the author believes that the company must maintain confidence in the brand to remain strong in mind and in accordance with customer expectations, which creates loyalty to the brand owner. The indicators used to measure customer loyalty due to confidence in the brand, namely a repeat purchase on a particular brand, the habit of consuming certain brands, pleasure in a particular brand, steadiness on specific brands, assuming the specific brand is the best and recommend a particular brand to others. The results showed the model of linear regression equation Y = 11.962 + 0,605X, with a very significant t-test and test of determination R2 = 0.427. The conclusion that confidence in the brand significantly positively affects customer loyalty amounted to 42.7%, and other factors determine the remaining 57.3%.